APPLICATION OF ABC AND XYZ-ANALYSIS TO OPTIMIZE RECEIVABLES (ON THE EXAMPLE OF "KOMUNPOSTACH" LLC) (ІННОВАЦІЙНА ЕКОНОМІКА, 2020)
Данилків Х.П., Горбова Х.В., Пайда Ю.Ю. ЗАСТОСУВАННЯ АВС ТА XYZ-АНАЛІЗУ ДЛЯ ОПТИМІЗАЦІЇ ДЕБІТОРСЬКОЇ ЗАБОРГОВАНОСТІ (НА ПРИКЛАДІ ТОВ «КОМУНПОСТАЧ»)Мета. Детальний аналіз впливу дебіторської заборгованості на господарську діяльність суб’єктів в умовах ринкових відносин та надання конкретних рекомендацій щодо їх ефективного використання та обігу у діяльності ТОВ «Комунпостач».Методика дослідження. У процесі дослідження використано загальнонаукові та спеціальні методи наукового пізнання, а саме: критичного аналізу, наукової абстракції та узагальнення наукового досвіду із сучасних теоретичних досліджень (при вивченні теоретичних засад та наукових підходів до управління дебіторською заборгованістю); статистичного аналізу (при узагальненні тенденцій, умов та особливостей формування дебіторської заборгованості, управління дебіторською заборгованістю підприємства ТОВ «Комунпостач»); класифікаційно-аналітичний та абстрактно-логічний (розробці концептуальної моделі управління дебіторською заборгованістю підприємства ТОВ «Комунпостач»); оптимізації (при моделюванні структури дебіторської заборгованості ТОВ «Комунпостач»); графічний (для наочного та схематичного відображення теоретичних і практичних результатів дослідження).Результати дослідження. Наведено рекомендації щодо поліпшення управління дебіторською заборгованістю ТОВ «Комунпостач». Зокрема, згруповано методом АВС-аналізу дебіторів підприємства. Запропоновано метод переходу до комбінованої політики фінансування оборотних активів, яка дасть змогу оптимізувати терміни та обсяги кредиторської заборгованості ТОВ «Комунпостач».Наукова новизна результатів дослідження. Удосконалено методичний підхід до прийняття управлінських рішень щодо оптимізації дебіторської заборгованості підприємств за товари на основі моделювання її структури за рахунок групування контрагентів за критеріями своєчасності погашення заборгованості, у якому, на відміну від існуючих, ураховуються як мікроекономічні, так і макроекономічні фактори впливу на динаміку частки простроченої дебіторської заборгованості, що надає можливість підвищити ступінь обґрунтованості рішень у відносинах підприємства з дебіторами.Практична значущість результатів дослідження. Постійне розширення кредитного ринку України та поява нових форм боргових і кредитних відносин у практиці вітчизняних підприємств, разом зі змінами зовнішнього оточення та складної системи нормативно-правових актів, потребують від підприємств нових методичних підходів до управління дебіторською заборгованістю. Науково обґрунтована система управління дебіторською заборгованістю може стати вагомим внеском у підвищення ефективності діяльності будь-якого підприємства.Ключові слова: дебіторська заборгованість; АВС та XYZ-аналіз; матриця; ресурси підприємства; зобов’язання і боргові вимоги; управління дебіторською заборгованістю. Данилкив К.П., Горбова К.В., Пайда Ю.Ю. ПРИМЕНЕНИЕ АВС И XYZ-АНАЛИЗА ДЛЯ ОПТИМИЗАЦИИ ДЕБИТОРСКОЙ ЗАДОЛЖЕННОСТИ (НА ПРИМЕРЕ ООО «КОМУНПОСТАЧ»)Цель. Цель исследования заключается в детальном анализе влияния дебиторской задолженности на хозяйственную деятельность субъектов в условиях рыночных отношений и предоставления конкретных рекомендаций по их эффективному использованию и обороту в деятельности ООО «Комунпостач».Методика исследования. В процессе исследования использованы общенаучные и специальные методы научного познания, а именно: критического анализа, научной абстракции и обобщения научного опыта из современных теоретических исследований (при изучении теоретических основ и научных подходов к управлению дебиторской задолженностью); статистического анализа (при обобщении тенденций, условий и особенностей формирования дебиторской задолженности, управление дебиторской задолженностью предприятия ООО «Комунпостач»); классификационно-аналитический и абстрактно-логический (разработке концептуальной модели управления дебиторской задолженностью предприятия ООО «Комунпостач»); оптимизации (при моделировании структуры дебиторской задолженности ООО «Комунпостач»); графический (для наглядного и схематического отображения теоретических и практических результатов исследования).Результаты исследования. Приведены рекомендации по улучшению управления дебиторской задолженностью ООО «Комунпостач». В частности, сгруппированы методом АВС-анализа дебиторы предприятия. Предложен метод перехода к комбинированной политики финансирования оборотных активов, которая позволит оптимизировать сроки и объемы кредиторской задолженности ООО «Комунпостач».Научная новизна результатов исследования. Усовершенствован методический подход к принятию управленческих решений по оптимизации дебиторской задолженности предприятий за товары на основе моделирования ее структуры за счет группировки контрагентов по критериям своевременности погашения задолженности. В нем, в отличие от существующих методических подходов, учитываются как микроэкономические, так и макроэкономические факторы влияния на динамику доли просроченной дебиторской задолженности. Это дает возможность повысить степень обоснованности решений в отношениях предприятия с дебиторами.Практическая значимость результатов исследования. Постоянное расширение кредитного рынка Украины и появление новых форм долговых и кредитных отношений в практике отечественных предприятий, вместе с изменениями внешнего окружения и сложной системы нормативно-правовых актов, требуют от предприятий новых методических подходов к управлению дебиторской задолженностью. Научно обоснованная система управления дебиторской задолженностью может стать весомым вкладом в повышение эффективности деятельности любого предприятия.Ключевые слова: дебиторская задолженность; АВС и XYZ-анализ; матрица; ресурсы предприятия; обязательства и долговые требования; управление дебиторской задолженностью. Danylkiv Kh.Р., Gorbovа Kh.V. Paida Yu.Yu. APPLICATION OF ABC AND XYZ-ANALYSIS TO OPTIMIZE RECEIVABLES (ON THE EXAMPLE OF "KOMUNPOSTACH" LLC)Purpose. The aim of the article is to carry out a detailed analysis of the effect of receivables on the economic activity of the entities in terms of market relations and providing specific recommendations on their effective use and circulation in the activities of LLC "Komunpostach".Methodology of research. General and special methods of scientific knowledge are used in the course of the research, namely: critical analysis, scientific abstraction and generalization of scientific experience from modern theoretical researches (while studying theoretical principles and scientific approaches to the management of accounts receivable); statistical analysis (in generalization of trends, conditions and peculiarities of the formation of accounts receivable, management of accounts receivable of the enterprise of "Komunpostach" LLC); classification and analytical, abstract and logical (development of conceptual model of receivables management of the enterprise of “Komunpostach” LLC); optimization (when modelling the structure of accounts receivable of Komunpostach LLC); graphic (for visual and schematic reflection of theoretical and practical research results).Findings. The recommendations for improving the receivables management of "Komunpostach" LLC are given. In particular, it is grouped by the method of ABC analysis of corporate debtors. The method of transition to the combined policy of financing of current assets is offered, which will allow to optimize terms and amounts of accounts payable of "Komunpostach" LLC.Originality. Methodical approach to managerial decision making on optimization of accounts receivable for goods based on modelling of its structure by grouping counterparties by the criteria of timely debt repayment, in which, unlike the existing ones, both microeconomic and macroeconomic factors are taken into account receivables, which makes it possible to increase the degree of validity of decisions in the relationship of the company with the debtors.Practical value. The constant expansion of the credit market of Ukraine and the emergence of new forms of debt and credit relations in the practice of domestic enterprises, together with changes in the external environment and a complex system of legal acts, require the enterprises new methodological approaches to the management of accounts receivable. A scientifically sound debt management system can make a significant contribution to improving the efficiency of any business.Key words: Accounts Receivable; ABC and XYZ analysis; Matrix; Enterprise Resources; Liabilities and Debt Requirements; Accounts Receivable Management.
Keywords: Key words; Accounts Receivable; ABC and XYZ analysis; Matrix; Enterprise Resources; Liabilities and Debt Requirements; Accounts Receivable Management.